Diatoms, silicoflagellates, and ebridians at Site U1341 on the western slope of Bowers Ridge, IODP Expedition 323. (March 2016) - Onodera, Jonaotaro; Takahashi, Kozo; Nagatomo, Ryoma
Abstract: The biostratigraphy and datum levels of diatoms, silicoflagellates, and ebridians are presented at Site U1341 drilled by the IODP Expedition 323 on the western slope of Bowers Ridge in the Bering Sea. Identified biostratigraphic diatom zones were from the Neodenticula seminae Zone to the Thalassiosira oestrupii Subzone. Silicoflagellate and ebridian zones were from the Distephanus octangulatus Zone to the Distephanus jimlingii Zone. The bottom age in the deepest Hole U1341B is estimated between 4.1 Ma and 5.0 Ma. Based on the succession of microfossil assemblages throughout the studied holes, the changes in paleoceanographic conditions are outlined.